Basal-Like Subgroup is Associated with Younger Age, Increased Expression of Androgen Receptor, and Worse Prognosis, while Non-basal-like Subtype is Associated with Higher BMI in Triple-Negative Breast Cancer Patients - Ibnu Purwanto; Didik Setyo Heiyanto; Ahmad Ghozali; Irianiwati Widodo; Iwan Dwiprahasto; Teguh Aryandono; Sofia Mubarika Haryana (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Triple-negative breast cancer (TNBC) represents a heterogenous disease which differ in characteristic, treatment response and prognosis. We aim to perform in-depth analysis on the clinicopathologic feature and the prognostic value of basal-like and non-basal-like TNBC patients in an Indonesian tertiary hospital.METHODS: We retrospectively included patients diagnosed with TNBC between 2014-2017. Clinical variables were collected from medical record. Expression of epidermal growth factor receptor (EGFR), cytokeratin 5/6 (CK5/6), p53 mutant and androgen receptor (AR) were examined by using immunohistochemistry (IHC).RESULTS: We included 67 subjects, 67.1% were basal-like and the remaining 32.9% were non-basal-like, with mean age of 51 years old, 59.7% subjects had BMI <25 and 40.3% subjects had BMI ≥25; 16.4%, 65.7%, and 17.9% subjects presented with early stage, locally advanced stage, and distant metastasis respectively; T<5 cm was found in 29.9% subjects, while 70.1% subjects had T≥5; 67.2% subjects presented with N-, while 32.8% subjects were N+. The most common histological type was infiltrating ductal (82% of subjects). P53 mutant and AR expressions were positive in 44.8% and 15% subjects, respectively. Basal-like subtype presented with younger age at and had higher expression of AR, while non-basal-like subtype is associated with BMI ≥25 (p<0.05). Basal-like subjects had shorter overall survival (23.9 months (95% CI: 21.9-25.9) vs. 26.1 months (95% CI: 23-29.2).CONCLUSION: Basal-like subtype is associated with worse prognosis, younger age at diagnosis and increased expression of AR, while non-basal-like subtype is associated with higher BMI in Indonesian TNBC.KEYWORDS: TNBC, subtype; basal-like, young age, Indonesia